Queer Roots for the Diaspora Ghosts in the Family Tree - Hayes, Jarrod Landin (University of Michigan Press, 2016)
Employing rootedness as a way of understanding identity has increasingly been subjected to acerbic political and theoretical critiques. Politically, roots narratives have been criticized for attempting to police identity through a politics of purity-excluding anyone who doesn't share the same narrative. Theoretically, a critique of essentialism has led to a suspicion against essence and origins regardless of their political implications. The central argument of Queer Roots for the Diaspora is that, in spite of these debates, ultimately the desire for roots contains the "roots" of its own deconstruction. The book considers alternative root narratives that acknowledge the impossibility of returning to origins with any certainty; welcome sexual diversity; acknowledge their own fictionality; reveal that even a single collective identity can be rooted in multiple ways; and create family trees haunted by the queer others patrilineal genealogy seems to marginalize.